2007
DOI: 10.1161/circulationaha.106.685503
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminal Provasopressin (Copeptin) as a Novel and Prognostic Marker in Acute Myocardial Infarction

Abstract: Background-The role of the vasopressin system after acute myocardial infarction is unclear. Copeptin, the C-terminal part of the vasopressin prohormone, is secreted stoichiometrically with vasopressin. We compared the prognostic value of copeptin and an established marker, N-terminal pro-B-type natriuretic peptide (NTproBNP), after acute myocardial infarction. .003) were significant independent predictors of death or heart failure at 60 days. The area under the receiver operating characteristic curves for cope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
274
4
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 338 publications
(311 citation statements)
references
References 27 publications
24
274
4
6
Order By: Relevance
“…While several markers, such as NT-BNP, 5,20,21 CRP, [21][22][23][24] D-Dimers, 20,25,26 Interleukin-6, 21,24,27 von Willebrand factor, 28, 29 S-100β, 30 and neuron specific enolase (NSE), 31 have been associated with functional outcome or mortality, only a few biomarkers added to prognosis based on clinical assessment. None of these markers, however, were fully evaluated including assessment of accuracy (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While several markers, such as NT-BNP, 5,20,21 CRP, [21][22][23][24] D-Dimers, 20,25,26 Interleukin-6, 21,24,27 von Willebrand factor, 28, 29 S-100β, 30 and neuron specific enolase (NSE), 31 have been associated with functional outcome or mortality, only a few biomarkers added to prognosis based on clinical assessment. None of these markers, however, were fully evaluated including assessment of accuracy (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Copeptin is a reliable prognostic marker not only in stroke patients but also in patients with cardiovascular events. 5,6 However, before implementing copeptin in clinical practice, the prognostic potential of copeptin needs to be validated in a prospective, independent, large multicenter study. Moreover, it is unclear whether copeptin predicts outcome in patients with ischemic stroke that has been treated differently, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Together with AVP, copeptin is derived from a 164-amino-acid precursor termed preprovasopressin, which consists of a signal peptide, AVP, neurophysin II and copeptin; thus, copeptin is the C-terminal part of pro-AVP. 45 Copeptin levels are elevated after an AMI 98 and are associated with left ventricular dysfunction and remodelling and clinical heart failure post AMI. 99 Copeptin levels are affected by gender and renal function.…”
Section: Copeptinmentioning
confidence: 99%
“…Distinct control of copeptin and NT-proBNP secretion could have potentially contributed to their additive effect on risk stratification. Indeed, Khan et al (2007) reported that NT-proBNP and copeptin showed similar accuracy in predicting death or HF in acute myocardial infarction; however, this combination in a multimarker risk stratification approach provided greater predictive accuracy.…”
Section: Discussionmentioning
confidence: 99%